Salinity and pH effects on survival, growth, and reproduction of quagga mussels - Seitz,Carina; Scordo,Facundo; Suenaga,Erin; Carlson,Emily M.; McMillen,Shaye; Gregory,Logan; Chandra,Sudeep (PeerJ, 2023)
Background In recent decades, invasive quagga mussels have expanded to the Western United States from the Great Lakes region of North America. Most studies that evaluate the invasion potential of quagga mussels in western water bodies have utilized physiological and life history information from zebra mussels, a related taxon. Few studies have assessed the potential for invasion using specific information from quagga mussel life history or experiments that test for their survival in the fresh and saline waters of the western United States. Methods We investigated quagga mussel survival, growth, and reproduction using semi-natural experiments under temperature and light controlled conditions across a gradient of water salinity (fresh to brackish) and pH (8.4–11). Water from Lake Mead was used as a positive control in our experiment, and water from Pyramid Lake and the Truckee River was used as brackish and freshwater treatments, respectively. The mussels used in the experiments were collected from Lake Mead. Results After 12 h in brackish water (4 ppt, pH 9.3), we observed 100% mortality of adult mussels. The swelling and disintegration of body tissues and high mortality rates indicated that high potassium, sodium, and chloride concentrations were the likely causes of death in brackish water treatments. In contrast, mussels were able to survive, grow, and reach sexual maturity in freshwater (0.1 ppt) with a low calcium concentration (17 mg L−1) after 57 days. Mussels died after 2 days at pH 11 and after 12 days at pH 10; during the 14-day monitoring period, no mortality was detected at pH 9.0, 9.3, or 9.5 and mussels did not exhibit any visual indications of stress. Understanding quagga mussel physiological and environmental tolerances appears to be essential for assessing their invasion potential in aquatic habitats.
Keywords: Invasive species; Quagga mussel; Dreissena spp; Freshwater lake; Brackish lake; Salinity; pH